2005
DOI: 10.1057/palgrave.thr.6040041
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Internet on Travel Agencies in Taiwan

Abstract: Travel and tourism-related products and services are highly compatible with the internet with the result that travel and tourism is one of the highest revenue-generating sectors of the internet. The rapid growth of the internet is having an impact on the distribution of travel services and has heightened speculation about the potential for disintermediation of the travel agent. This research investigates the impact of the internet on the distribution of travel services and the extent to which it has influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 15 publications
0
40
0
2
Order By: Relevance
“…As more people began to buy holiday packages from the Internet, researchers started to look at the disintermediation of travel agents. Bennett and Lai (2005) identified two principal ways for travel agents to overcome disintermediation; namely, repositioning themselves as travel consultants and becoming more technologically oriented. Some travel agencies have formed strategic alliances to strengthen their competitive advantage in the era of Internet (Huang, 2006).…”
Section: Journal Of Travel and Tourism Marketingmentioning
confidence: 99%
“…As more people began to buy holiday packages from the Internet, researchers started to look at the disintermediation of travel agents. Bennett and Lai (2005) identified two principal ways for travel agents to overcome disintermediation; namely, repositioning themselves as travel consultants and becoming more technologically oriented. Some travel agencies have formed strategic alliances to strengthen their competitive advantage in the era of Internet (Huang, 2006).…”
Section: Journal Of Travel and Tourism Marketingmentioning
confidence: 99%
“…According to Cai et al, (2004) and Chen and Yen, (2004) the main factors that need to be focused on in order to build the confidence of travel agencies in using the web as an effective marketing tool are security issues and the required technology. Bennett and Lai (2005) based on a quantitative study on the impact of the web on travel agencies in Taiwan found that the main obstacles faced by travel agencies were the high capital costs required in contrast to the small number of bookings online and the difficulty of recruiting skilled labour with IT and marketing knowledge. Costs and inadequate knowledge were also found by cited as critical barriers to web use for business purposes by Ghanaian hotels (Ayeh, 2006).…”
Section: Challenges Of Web Use In the Tourism Industrymentioning
confidence: 99%
“…Re-intermediation or cybermediation has been defined as the "utilization of ICT and web tools for the development of either new intermediaries or new methods for existing intermediaries that enable them to re-engineer the tourism distribution channel" (Bennett and Buhalis, 2003). According to Bennett and Lai (2005) the web is presenting opportunities for new electronic intermediaries. Based on the premise that intermediaries exist because they provide value-added services, these then have the potential to pass economies of scale directly to consumers, offering reduced fares as well as convenience of making reservations on a 24/7 basis.…”
Section: Impact Of the Web On Distribution In The Tourism Industrymentioning
confidence: 99%
“…The huge number of online travelers also encourages hotels as well as other suppliers, such as airlines, to reconsider the adoptions of the e-business technologies not as an extra cost but as a strategic investment (Buhalis and Licata, 2002). Consequently, as the searching and buying transactions are made easier, and travelers become more computer literate, it may well be that the travel agencies' power on the distribution channels will be diminished gradually unless they can offer value added advice, such as travel advice which satisfies the customer needs (Lewis, Semeijn, and Talalayevsky, 1998; Bennett and Lai, 2005). Such a situation is also discerned in the survey of European online travel market, conducted by Eyefortravel in 2007 that revenue generated by online travel agents is eroded by the more online-aggressive suppliers.…”
Section: Disintermediation In Literaturementioning
confidence: 99%
“…Through the consideration of the tourism stakeholders and the tourism value chain, this paper underlines that disintermediation is not an issue between suppliers and intermediaries only. Rather, it is essentially about customers too since they are the most powerful component of the tourism supply chain, especially in this Internet-enabled era (Bennett and Lai, 2005;Buhalis and Law, 2008). The three case studies reflect interrelation among the three main components of the tourism supply chain, while other prior studies focused more on the relationship between travel agents and suppliers and ignored the importance of customers.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%